Parenting Approaches and Emotional-Mental in Children with Speech Delay - fitriasari, andikawati; Sari, Dewi Utama; Zahroh, Chilyatis; Faizah, Imamatul; Hidayaah, Nur (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2025)
The development of children's speech skills that have not developed according to their age stage is strongly influenced by family factors, parenting patterns. Children with speechdelay have difficulty expressing their feelings are very vulnerable to mental emotional problems. The purpose of this study aims to analyze the relationship between parenting patterns and mental emotions in speechdelayed children. Correlational analytic research with a cross-sectional approach. The population was 170 parents and the sample was 63 respondents of parents and children. with consecutive sampling technique. The independent variable is parenting style and the dependent variable is mental emotional of specchdelay children. The instrument used parenting patterns using The Parenting Style and Dimension Questionnaire (PSDQ) while the mental emotional questionnaire uses the Strength and Difficulties Questionnaire (SDQ) version 4-10 years. Data analysis used Chi-square test with a significance level of α<0.05. The results showed 63 parents of speechdelayed children 25 parents applied democratic parenting and 26 children had normal mental emotional. The results of the chi-square test p = 0.000 which means p < α, then H0 is rejected and H1 is accepted, meaning that there is a relationship between parenting patterns and mental emotions in speechdelayed children. Parenting that does not support optimal language development is one of the main determinants in cases of speech delay in children ABSTRAK Perkembangan kemampuan bicara anak yang belum berkembang sesuai dengan tahap usianya sangat dipengaruhi oleh factor keluarga, pola asuh orang tua. Anak dengan speechdelay sulit mengekspresikan perasaannya sangat rentan mengalami masalah mental emosional. Tujuan penelitian ini bertujuan menganalisis hubungan antara pola asuh dengan mental emosional pada anak speechdelay. Jenis penelitian analitik korelasional dengan pendekatan cross-sectional. Populasi sejumlah 170 orang tua dan sampel sebanyak 63 responden orang tua serta anak. dengan teknik sampling consecutive sampling. Variabel independent yaitu pola asuh orang tua dan variable dependen mental emosional anak specchdelay. Instrumen yang digunakan pola asuh orang tua menggunakan The Parenting Style and Dimension Questionnaire (PSDQ) sedangkan kuesioner mental emosional menggunakan Strength and Difficulties Questionnaire (SDQ) versi 4-10 tahun. Analisis data menggunakan Uji Chi-square dengan tingkat signifikansi α<0,05. Hasil penelitian menunjukkan 63 orang tua dari anak speechdelay 25 orang tua menerapkan pola asuh demokratis dan 26 anak memiliki mental emosional normal. Hasil uji chi-square p = 0,000 yang berarti p < α, maka H0 ditolak dan H1 diterima artinya ada hubungan pola asuh dengan mental emosional pada anak speechdelay. Pengasuhan yang tidak mendukung perkembangan bahasa secara optimal merupakan salah satu determinan utama dalam kasus keterlambatan bicara pada anak.